Eksistensi Riba dan Qimar dalam Pasal 48 Ayat (5) PP No 25 Tahun 2018 Tentang Pelaksanaan Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf: The Presence of Riba and Qimar in Article 48(5) of Government Regulation No. 25 of 2018 on the Implementation of Law No. 41 of 2004 on Waqf - Khoir Affandi (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
In his article, this journal will discuss about qimār and usury in Islamic waqf investment in Islamic banks outside. According to researchers Article 43 Paragraph (1) of Law Number 41 of 2004 concerning Waqf which reads the management and development of endowments by Nazhir approved by Article 42 carried out in accordance with sharia principles, as opposed to Article 48 Paragraph (5) Government Regulation Number 25 Year 2018 About the Implementation of Law 41 of 2004 concerning Waqf which reads the management and development of endowment assets made in the form of investment in Islamic banks must be insured with Islamic insurance. Qualitative research methods that use historical and legal research, as for the type of data used are primary data, secondary data and tertiary data and the research method used is descriptive analysis method, with data collection techniques used are library studies. The settlement of the harmonization of legal norms is carried out by using legal reforms with the renewal of the Government Regulation on the Implementation of the Waqf Law, by other means by questioning the judicial review to the judiciary with the principle of legal certainty, the principle of expediency and legal principles, or with the help of the Lexus legal doctrine. derogate superior inferior legions. Because for the endowment money money for that money forever it is necessary to make money for immovable property, but for a temporary endowment the money can only be lent.